2016
DOI: 10.1128/aac.00358-16
|View full text |Cite
|
Sign up to set email alerts
|

PBP 4 Mediates High-Level Resistance to New-Generation Cephalosporins in Staphylococcus aureus

Abstract: bStaphylococcus aureus is an important cause of both hospital-and community-associated methicillin-resistant S. aureus (MRSA) infections worldwide. ␤-Lactam antibiotics are the drugs of choice to treat S. aureus infections, but resistance to these and other antibiotics make treatment problematic. High-level ␤-lactam resistance of S. aureus has always been attributed to the horizontally acquired penicillin binding protein 2a (PBP 2a) encoded by the mecA gene. Here, we show that S. aureus can also express high-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 43 publications
1
49
0
1
Order By: Relevance
“…We have previously shown that passage of the COLnex strain in ceftobiprole (generating strain CRB) resulted in resistance to both ceftobiprole and ceftaroline, with the MICs being 128 g/ml and 64 g/ml, respectively ( Table 1), and that resistance was associated with two amino acid substitutions, E183A and F241R, in PBP4 (3,4). Resistance was also associated with a markedly increased amount of PBP4 in whole-cell lysates and membrane proteins of CRB compared with the amount in COLnex ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that passage of the COLnex strain in ceftobiprole (generating strain CRB) resulted in resistance to both ceftobiprole and ceftaroline, with the MICs being 128 g/ml and 64 g/ml, respectively ( Table 1), and that resistance was associated with two amino acid substitutions, E183A and F241R, in PBP4 (3,4). Resistance was also associated with a markedly increased amount of PBP4 in whole-cell lysates and membrane proteins of CRB compared with the amount in COLnex ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance to ␤-lactam antibiotics seen in MRSA is especially serious as they remain the most widely prescribed class globally, typically having a favorable safety profile and being relatively affordable and accessible. Although broad-spectrum MRSA resistance to ␤-lactam antibiotics has long been attributed to impaired acylation of the mecA gene product, penicillin-binding protein 2a (PBP2a) (2), recent evidence shows penicillin-binding protein 4 (PBP4), a low-molecular-weight monofunctional transpeptidase, can facilitate antibiotic resistance independently of PBP2a (3)(4)(5)(6)(7)(8)(9). It has been previously demonstrated that the only essential penicillinbinding proteins (PBPs) in S. aureus are the monofunctional highmolecular-weight transpeptidase, PBP1, and the bifunctional PBP2 (glycopolymerase/transpeptidase) (10).…”
mentioning
confidence: 99%
“…Analogous to alternative PBP usage in methicillin resistant Staphylococcus aureus (55,56), we find a key consequence of environment-driven plasticity in E. coli cell wall metabolism is intrinsic resistance to β-lactam antibiotics with a narrow target specificity. The most commonly prescribed class antibiotics, β-lactam antibiotics are frequently used to treat E. coli infections, including in treatment of urinary tract infections.…”
Section: Discussionmentioning
confidence: 84%